Use of Picture Card Media to Improve Beginning Reading Skills of Elementary Students - Ahmad Wahyudi (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research is motivated by the lack of interest in reading students and the lack of beginning reading skills, all because reading skills are good and right for everyone to have. Not only in reading skills, but writing, speaking and listening skills are also important in learning. In Indonesian language learning, which includes basic competencies and core competencies. The use of media is very important to support a learning activity in order to achieve a planned goal. This research aims to find out how the application of picture card media improves the beginning reading skills of Bhakti Negara grade 1 students. This type of research is classroom action research conducted in two cycles, with stages including planning, implementation, observation, and reflection. In cycle 1, learning was carried out without applying picture card media in learning with the achievement of completeness with a percentage of 55.25% with an average score below 70 from all grade 1 students. In cycle 2, which was carried out by using picture card media in learning, students achieved higher completeness than in cycle 1, with a percentage of 90.22% with an average above 75 from grade 1 students. Thus the use of picture card media is very helpful in improving the reading skills of grade 1 students at SDN Bhakti Negara.